Justice and Utility in The Regulation of The Crime of Adultery in Law Number 1 of 2023 - Hayatun Nufus (Proceeding International Conference on Social Sciences, 2026)
Developments in criminal law provide new insights into law enforcement in Indonesia. The enactment of Law Number 1 of 2023 concerning the Criminal Code (KUHP) is particularly interesting. One interesting aspect concerns the crime of adultery, which is punishable by criminal sanctions for unmarried couples upon a complaint from either party or their parents. These sanctions include imprisonment and fines, as stipulated in Law Number 1 of 2023. The legal research used is normative legal research. The purpose of this research is to provide insights into the adultery article from the perspective of legal objectives, namely justice and utility. The increasing number of adultery cases in Indonesia results in losses for all parties. Therefore, regulations regarding the crime of adultery can deter perpetrators or make them think twice before committing the act. Thus, legal objectives can be achieved in Indonesian society.